A Signaling Theory of Acquisition Premiums: Evidence from IPO Targets - Reuer, Jeffrey J.; Tong, Tony W.; Wu, Cheng-Wei (Academy of Management Journal, 2012)
This article extends signaling theory to research on acquisition premiums and investigates the value that newly public targets capture in post-IPO acquisitions. We complement previous research on acquisition premiums by suggesting that signals about targets can enhance sellers' gains by reducing acquirers' offer price discounting that is due to information asymmetries. Specifically, we argue that target firms can engage in interorganizational relationships (e.g., associations with prominent investment banks, venture capitalists, and alliance partners) that function as signals and enhance sellers' gains. Empirical evidence shows that the benefits of such signals apply to domestic and cross-border deals alike and that these benefits are even greater for IPO targets selling their companies to acquirers based in different industries.